Virtual Reality Integrated ew TPACK and PBL to Improve Critical Thinking Ability in Science Learning for Elementary School - Wika Putriana; Endang Widi Winarni; Abdul Muktadir; Endina Putri Purwandari (Jurnal Pendidikan Indonesia, 2026)
The gap in science learning in elementary schools remains a problem that impacts students' low critical thinking skills and scientific literacy, mainly due to teachers' limitations in preparing interactive learning media integrated with innovative learning models. This study aims to develop interactive media with Virtual Reality (VR) based on TPACK-PBL in science learning to improve critical thinking skills and scientific literacy of sixth grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE development model. The research subjects consisted of 15 students in the trial class and 20 students in the effectiveness test class. Quantitative data were obtained through validation by material, language, and graphics experts, product trials, and effectiveness tests using pretests and posttests, while qualitative data were obtained through interviews, observations, and questionnaires of teacher and student responses. The results of the study indicate that interactive media with VR based on TPACK-PBL is effective in improving students' critical thinking skills and scientific literacy. VR scenarios in problem-based learning are able to stimulate students to observe, collect virtual data, analyze information, and draw conclusions. The implications of this research indicate that TPACK-PBL-based learning design with VR support can be an innovative alternative to improve teacher competence, strengthen understanding of science concepts, and encourage students' abilities to solve real-world problems critically and scientifically.